Limiting the Carbon Footprint of an Enterprise: Calculation Methods and Solutions - Svetlana Ivanova; Elena Zhidkova; Alexander Prosekov (Qubahan Academic Journal)
The importance of the carbon footprint problem is determined by its role in global warming and climate change, which lead to various negative consequences (heavy rains, droughts, floods, other climatic disasters), as well as threaten human health and well-being. The fight against the carbon footprint problem requires a comprehensive approach, including improving energy efficiency, switching to renewable energy sources, improving emission reduction technologies, forest conservation and rational use of resources. This problem concerns everyone, consumers and producers. There are many points of contact between consumers and producers of goods and services that allow to jointly solve the global problem of the carbon footprint and work to create a sustainable and environmentally friendly planet. Existing changes are already having a significant impact on our world and will have even more serious consequences in the future if each of us, both consumer and producer, does nothing to reduce carbon emissions.